Sandburg's Lincoln The complete mini-series event (Mill Creek Entertainment Mill Creek Entertainment, 1974)
This is the story of the West as it has never been told before, myth and legend stripped away and the truth revealed by 17 of the nation's top Western authorities. Learn the truth about Billy the Kid, Jesse James, the Sundance Kid, and many more.
Sandberg's Lincoln, television's first broadcaster mini-series stars Hal Holbrook in his Emmy winning role in this dramatic adaption of Carl Sandburg's bestselling novel. Produced by the legendary David L. Wolper (Roots), this groundbreaking portrait follows Abraham Lincoln's life from his early years as a lawyer on the Illinois prairie to his rise in politics, highlighted by the election campaign that led him to the White House. The complete series depicting the lie story one of the most influential figures in American history is masterfully presented on home video for the first time ever in this 2 DVD collector's set featuring all 6 segments.
Sandburg's Lincoln
Rating: Not rated.
NTSC ; All regions.
Keywords: Crime -- West (U.S.) -- History; Frontier and pioneer life -- West (U.S.); Historical films; Outlaws -- West (U.S.) -- Biography; Peace officers -- West (U.S.) -- Biography; West (U.S.) -- History -- 1860-1890.; Documentary films